2016
DOI: 10.1186/s13018-016-0428-4
|View full text |Cite
|
Sign up to set email alerts
|

Eradication rates, risk factors, and implant selection in two-stage revision knee arthroplasty: a mid-term follow-up study

Abstract: BackgroundTwo-stage revision (TSR) knee arthroplasty is an established treatment, but failure to control infection still occurs in 4–50 % of cases. The aim of this study was to assess the infection eradication rate, risk factors for failure, and the clinical outcome after two-stage revision knee arthroplasty.MethodsThis retrospective study included 59 patients who had undergone at least one two-stage revision procedure due to periprosthetic joint infection (PJI). Demographic data, comorbidities, types of impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…The presence of a sinus tract and liver disease were patient characteristics associated with treatment failure, which have been demonstrated previously [10, 27]. Sinus tracts are often indicative of long-standing infection, which may make biofilm eradication challenging and further perturb bone stalk.…”
Section: Discussionmentioning
confidence: 52%
“…The presence of a sinus tract and liver disease were patient characteristics associated with treatment failure, which have been demonstrated previously [10, 27]. Sinus tracts are often indicative of long-standing infection, which may make biofilm eradication challenging and further perturb bone stalk.…”
Section: Discussionmentioning
confidence: 52%
“…Two-stage revision arthroplasty of infected prosthetic joints is commonly performed in North America as definitive treatment of PJI. 45 , 46 Determining whether a patient who has undergone the first stage of a staged revision arthroplasty is ready for reimplantation is a diagnostic dilemma. These patients have recently undergone explantation, typically in the six to eight weeks prior, which affects nonspecific inflammatory markers such as ESR and CRP.…”
Section: Resultsmentioning
confidence: 99%
“…The current gold standard for the treatment of chronic PJI is the two-stage revision, removing the original prosthesis and implanting the antibiotic cement spacer after thorough debridement; 4-6 weeks intravenous and 4-6 weeks oral antibiotic treatment follows, and a new prosthesis is implanted after the infection is controlled 3,16 . Drexler et al treated patients with chronic PJI with two-stage revision after TKA; the success rate of the two-stage revision surgery was up to 85.4% 17 .…”
Section: Discussionmentioning
confidence: 99%
“…treated patients with chronic PJI with two‐stage revision after TKA; the success rate of the two‐stage revision surgery was up to 85.4%. Hoell's study found that the two‐stage revision for chronic PJI of TKA had a success rate of 93.2% for 4 years of follow up. The two‐stage revision has a high success rate for TJI.…”
Section: Discussionmentioning
confidence: 99%